Impact of Patient-Prosthesis Mismatch following Aortic Valve Replacement on Long-Term Survival and Quality of Life - Hoffmann, Grischa; Abraham-Westphal, Selam; Attmann, Tim; Frank, Derk; Lutter, Georg; Cremer, Jochen; Petzina, Rainer (The Thoracic and Cardiovascular Surgeon, 2020)
Background The impact of patient-prosthesis mismatch (PPM) after aortic valve replacement (AVR) on long-term survival and quality of life (QoL) remains controversial. The objective of this study was to evaluate the impact of PPM on long-term survival and QoL in a large cohort of patients treated with isolated stented biological AVR in a single-center experience.Methods We analyzed data of 632 consecutive patients following isolated stented biological AVR between 2007 and 2012 at our institution. We evaluated the QoL (393 evaluable patients) using the Short Form 12-item Health Survey (SF-12) questionnaire via telephone call and the impact of PPM on long-term survival (533 evaluable patients) by Kaplan–Meier's estimate.Results Severe PPM (<0.65 cm2/m2) had a negative impact on physical component summary (PCS) score (SF-12) compared with patients with moderate or no PPM (p = 0.014), while the mental component summary (MCS) score (SF-12) was not affected by the degree of PPM (p = 0.133). Long-term survival was not different among the three different PPM groups investigated (p = 0.75).Conclusion Severity of PPM demonstrated no influence on long-term survival and MCS score (SF-12), but it was associated with a lower PCS score (SF-12) in patients with severe PPM.
Keywords: cardiac; heart valve surgery; quality of life; outcomes; includes mortality, morbidity